Otehive.co tote bag / Alyssa Gabrielle Lo … [et al.] - Lo, Alyssa Gabrielle; Sikajat, Gillian; Firmalis, Ahmad Salehur Raziqin Norfin; Rosli, Muhammad Syafiq; Abd Rahman, Nurul Laila ‘Ayunni; Abdul Azis, Rafidah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
In light of the constant problems revolving around traditional canvas tote bags, ToteHive.Co aims to bring a multi-functional tote bag that resolves the flaws of traditional by bringing our consumers much needed functionality and sustainability whilst still adhering to the aesthetic of traditional tote bags. As users of traditional tote bags, we have found that users battle with its functionality as well as it’s sustainability as items carried tend to be in a clutter and cannot hold as many items in one sitting. As an eco-friendly company, we want to change views of tote bags by giving users multi pockets inside and outside of the bag (laptop sleeve and bottle holder included) as well as including a water-resistant finish by using a Durable Water Repellent (DWR) finishing on the outer layer of bags to improve its sustainability. Our objectives are to provide our users with a sustainable, eco-friendly tote bag that has a high functionality whilst still maintaining the traditional aesthetic of canvas tote bags. We believe that our product has a high potential of commercialization as tote bags have been booming in the market and we want to put an edge to it’s design by answering the problems of tote bag users around the world.